Political Communication Practice of Cipayung Student Organization Kupang- NTT Province - Mas'amah Mas'amah; Emanuel Sowe Leuape; Juan Ardiles Nafie; Felisianus Efrem Jelahut; Saulus Ngabi Nggaba (Komunikator, 2023)
This study aimed to determine the practice of political communication carried out by the Cipayung student organization in the city of Kupang, East Nusa Tenggara Province. The research method used is qualitative with a case study approach. Data collection techniques in this study were in-depth interviews, observation, and documentation. Interviews were conducted with five key informants who are representatives of five organizations. The results of the study show that the practice of political communication carried out by the Cipayung student organization in the city of Kupang, East Nusa Tenggara Province, is implied through rhetorical messages in the nuances of a Political campaign that aims to build mutual understanding/agreement which will be strengthened through formal talks in meetings/political assembly in order to produce certain political decisions/attitudes. A number of things took place during the use and development of political communication strategies practiced by the various student organizations in their capacity as pressure groups. The various aspects include the construction of political messages, the choice and use of political communication media, the implementation of the political communication function, the obstacles faced in political communication, and the adoption of Information and Communication Technology innovations in the implementation of political communication.